Regulation of microglial activation in stroke - ZHAO Shou-cai; MA Ling-song; CHU Zhao-hu; XU Heng; WU Wen-qian; LIU Fudong (Acta Pharmacologica Sinica; Vol 38, No 4 (April 2017): Acta Pharmacologica Sinica, 2017)
When ischemic stroke occurs, oxygen and energy depletion triggers a cascade of events, including inflammatory responses, glutamate excitotoxicity, oxidative stress, and apoptosis that result in a profound brain injury. The inflammatory response contributes to secondary neuronal damage, which exerts a substantial impact on both acute ischemic injury and the chronic recovery of the brain function. Microglia are the resident immune cells in the brain that constantly monitor brain microenvironment under normal conditions. Once ischemia occurs, microglia are activated to produce both detrimental and neuroprotective mediators, and the balance of the two counteracting mediators determines the fate of injured neurons. The activation of microglia is defined as either classic (M1) or alternative (M2): M1 microglia secrete pro-inflammatory cytokines (TNFα, IL-23, IL-1β, IL-12, etc) and exacerbate neuronal injury, whereas the M2 phenotype promotes anti-inflammatory responses that are reparative. It has important translational value to regulate M1/M2 microglial activation to minimize the detrimental effects and/or maximize the protective role. Here, we discuss various regulators of microglia/macrophage activation and the interaction between microglia and neurons in the context of ischemic stroke.